Evolución de la política exterior de Estados Unidos desde el fin de la Segunda Guerra Mundial hasta el segundo gobierno de Donald Trump - Díaz Ligarda, Juan (2025)
Since the end of World War II, the world has been governed by a stable international order under the hegemony of the United States. However, in recent years, there have been signs that we may be on the verge of a new stage, yet to be defined. The election of Donald Trump as President of the United States for a second time has revived this idea, but it has also signaled a reorientation of U.S. foreign policy, which could have consequences for the rest of the world, as it would open the door to a phase of instability and uncertainty with profound political and economic repercussions. This article aims to provide a historical assessment of U.S. hegemony, including the challenges it has been facing, as well as to analyze the potential impact of its new foreign policy under Donald Trump’s administration.